Effect of zinc foliar application and mycorrhizal inoculation on morpho-physiological traits and yield parameters of two barley cultivars - Moshfeghi, Narjes; Heidari, Mostafa; Asghari, Hamid Reza; Baradaran Firoz Abadi, Mehdi; Abbott, Lynette K.; Chen, Yinglong (Italian Journal of Agronomy, 2019)
Zinc (Zn) plays a vital role in biological systems. Plants require an appropriate balance of this essential micronutrient for growth and optimum yield. This study focused on the effectiveness of foliar application of Zn combined with inoculation with arbuscular mycorrhizal (AM) fungi on morphological, physiological traits and yield parameters of barley cultivars during the 2015-2016 growing season. In this factorial experiment, different forms of foliar applied ZnO (nil, nano Zn, ordinary Zn and nano+ordinary Zn) and inoculation with AM fungi (nil, Glomus mosseae and Rhizophagus irregularis) were investigated for two barley cultivars (Yusuf and Julgeh). The two cultivars differed in response to the form of foliar Zn applied and inoculation with the two commercial inocula of AM fungi. The major responses were significant increases in chlorophyll content (107%), soluble sugar (227%), grain Zn concentration (217%), carbonic anhydrase activity (128%) and grain phytase activity (65%) for cultivar Julgeh inoculated with G. mosseae when sprayed with nano ZnO compared with control. Cultivar Julgeh inoculated with G. mosseae had physiological traits more likely to enhance productivity and economical yield than did cultivar Yusuf that invested more in root traits and vegetative growth. Consequently, the nano form of Zn positively increased root and shoot morphological parameters, physiological parameters and grain Zn concentration, but the ordinary form of Zn enhanced yields and yield parameters. While foliar Zn application and inoculation with AM fungi significantly enhanced all measured parameters, the forms of Zn and inoculation with the two different AM fungi differed in their effectiveness.